Safety and health management practices in SMEs in Harare - Zimbabwe - Mapetere, Denver; Sikomwe, Shingirai (IJECM Pub UK, 2021)
The aim of the study is to carry out an evaluation of the SHE practices being used by SMEs in Zimbabwe. Given the number of SMEs and the number of workplace related matters reported in the 2012 national survey, there is a clear need for a study to understand how SMEs are managing workplace safety and health matters. The study used a quantitative approach for data collection and analysis. A total of 48 SME owner/managers participated in the study. The results show that the majority of SMEs have not adopted or implemented safety and health promoting practices. Empirical findings from the study have shown that SMEs do not invest in safety and health promotion regardless of the nature of work, workforce size and prevalence of safety and health problems in their organisations. The study recommends that SMEs need to recognise the importance of an environment that promotes safety and health of their employees and to make considerable investments towards creating such an environment.